Effects of Damnacanthal, Nordamnacanthal, Betulinic Acid and Zerumbone Isolated from Local Medicinal Plants on Leukemia Cell Lines and Immune Cells - Abd Rahman, Mashitoh (2007)
The present study was to evaluate the toxicity and immunomodulatory effects of damnacanthal, nordamnacanthal, betulinic acid and zerumbone isolated from local medicinal plants towards leukemia cell lines and immune cells. Toxicity study was performed on HL-60 (Human acute promyelocytic leukemia), CEM-SS (Human T-lymphoblastic leukemia), WEHI-3B (Mouse myelomonocyte leukemia), 3T3 (Mouse embryo fibroblast) and human peripheral blood mononuclear cell (PBMC) by using MTT assay and cell cycle analysis. The results showed that damnacanthal significantly inhibited HL-60 cells, CEM-SS and WEHI-3B with the IC50 value of 4.0 μg/mL, 8.0 μg/mL and 3.3 μg/mL, respectively. Nordamnacanthal and betulinic acid showed stronger inhibition towards CEM-SS and HL-60 cells with the IC50 value of 5.7 μg/mL and 5.0 μg/mL, respectively. In contrast, Zerumbone was demonstrated to be more toxic towards those leukemia cells with the IC50 value less than 10 μg/mL. Interestingly, damnacanthal, nordamnacanthal and betulinic acid were not toxic towards 3T3 and PBMC compared to doxorubicin which showed toxicity effects towards 3T3 and PBMC with the IC50 value of 3.0 μg/mL and 28.0 μg/mL, respectively. The cell cycle analysis exhibited that damnacanthal exerted its toxicity effect towards HL-60 cells by inducing apoptosis with value of 25% after 72 hours treatment. Immunomodulatory study revealed that damnacanthal, nordamnacanthal, betulinic acid and zerumbone were able to stimulate the proliferation of mice thymocytes, mice splenocytes and PBMC in a time and dose-dependent fashion. Damnacanthal and nordamnacanthal were able to stimulate the proliferation of mice thymocytes, mice splenocytes and PBMC even at low concentration (0.46 μg/mL) and did not cause inhibition at higher concentration (30 μg/mL). In contrast, betulinic acid and zerumbone showed inhibition at higher concentration (30 μg/mL) and proliferate well at lower concentration (7.5 μg/mL) towards those immune cells. Results obtained from cell cycle analysis exhibited that the proliferation effect of those compounds on PBMC were corresponding with the MTT based lymphocyte proliferation assay. Moreover, those compounds were demonstrated to induce immunoregulatory cytokine production in highest degree of human IL-2 and in lower degree of human IL-12 upon stimulation of PBMC in a time dependent manner. Based on the result presented, the compounds damnacanthal, nordamcanthal, betulinic acid and zerumbone can act as cytotoxic and immunomodulatory agent which are very useful in treating cancer and enhancing the immune system.